Opportunity for receptor antagonist of interlеukin-1 to prevent neurological complication of pancreatic diabetes - Супрун, О. С. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
On the model of alloxan diabetes in rats there was studied the effect of thiocetam and receptor antagonist of interleukin-1 (RAIL-1) (7.5 mg/kg) on the performance of oxidative modification of proteins (OMP), thiol-disulfide system (TDS) and energy metabolism. It was founded that development of hyperglycemia in experimental animals was accompanied with increase of levels of OMP markers – AFG and CFK, decrease of activity of enzymes of TDS (glutathionperoxidase and glutathionreductase), multiway changes in thiol-disulphide balance (increased levels of oxidized glutathione and thiols on a background of sharp decrease of their oxidative forms) and increase of neurotoxical homocysteine and nitrotyrosine. It was proved that the course of administration of thiocetam and RAIL-1 contributed to the stabilization of indicators of OMP and TDS, normalization of activity of glutathionperoxidase and glutathionreductase, decrease of levels of homocysteine and nitrotyrosine, the maximum activity was observed in RAIL-1. Ranging of studied parameters was made; at development of alloxan diabetes there were identified the most significant changes in these parameters and degree of their correction in experimental therapy with thiocetam and RAIL-1, and significant correlations were found.